KINERJA MICROBIAL FUEL CELLS PADA PENGOLAHAN LIMBAH CAIR PEMINDANGAN DENGAN MEMBRAN SEPARATOR CAMPURAN POLIMER KITOSAN/PVA - Bustami Ibrahim, Pipih Suptijah, dan Fajar Syahreza (Jurnal Teknologi Industri Pertanian, 2017)
Separator attched to MFC system can reduce the distance between cathode and anode and limit oxygen penetration to anode chamber. The use of Chitosan/polyvinyl alcohol (PVA) mixture polymer as membrane separator was expected to have ability to increase electron recovery from the substrate. The objectives of this research were to increase the standard quality of wastewater of salted boiled fish processing and to increase bioelectricity generation, through the membrane separator adding to MFC system. Separator polymer was made by blending 2% chitosan and 5% PVA solution, in different ratio of chitosan (K) and PVA (P) at 2:3 (K2P3), 1:1 (K1P1), 3:2 (K3P2), and without separator. The study was carried out to measure electricity generated and to analyse of BOD, COD and TAN of the wastewater.  The K2P3 treatment showed the highest electricity generation with average voltage of 0.50±0.06 V, maximum current density 0,29 mA/cm2, and  maximum power density  15.40 mW/cm2. The reduction of COD showed insignificantly different among treatments, but the reduction of BOD and TAN values showed significantly different. The BOD value reduced to56.54% in K2P3 treatment and the TAN value reduced to 92.73% in K1P1 treatment.Keywords : chitosan, microbial fuel cell, polyvinil alcohol, separator